Jawabanmu

Jawaban paling cerdas!
2014-02-22T11:12:23+07:00
F(x) = 2x^2 - 1
g(x) = cos x

f(g(x)) ?

f(cos x)
2(cos x)^2 - 1
2(cos^2 x) - 1
2cos^2 x - 1

CMIIW
ohiyak. bentar

(fog)(x) = 3x^2 - 3x + 4
f(g(x)) = 3x^2 - 3x + 4
f(x^2 - x + 3) = 3x^2 - 3x + 4
f(x^2 - x + 3) = 3x^2 - 3x + 9 - 5
f(x^2 - x + 3) = 3(x^2 - x + 3) - 5

f(x) = 3x - 5

CMIIW
Komentar sudah dihapus
Komentar sudah dihapus
plajaran kimia bisa gak ?
ngga :3
2014-02-22T13:10:59+07:00

(fog)(x) = 3x^2 - 3x + 4
f(g(x)) = 3x^2 - 3x + 4
f(x^2 - x + 3) = 3x^2 - 3x + 4
f(x^2 - x + 3) = 3x^2 - 3x + 9 - 5
f(x^2 - x + 3) = 3(x^2 - x + 3) - 5

f(x) = 3x - 5

CMIIW